The developing of e-commerce and the role of digital marketing in Uzbekistan - Mirsoleyeva Samira (American Journal of Economics and Business Management, 2024)
Marketing of products and services continues to be one of the areas that require constant innovation around the world today. An important marketing strategy these days is digital marketing, defined as the use of electronic media by marketers to introduce products and services to the e-commerce platforms, with the main objective of attracting consumers and connecting them to the brand through digital media. For data collection, this is an exploratory analysis focused on statistical data, economic comparison and data grouping. The findings imply that managers can create and execute more effective business strategies while interacting with prospective Uzbek clients. This research broadens our knowledge of Uzbek culture and how it influences consumer behaviour, which is an important aspect of marketing.